Nasogastric Feeding Tubes May Not Contribute to Gastroesophageal Reflux in Preterm Infants - Murthy, Swati V.; Funderburk, Apryle; Abraham, Sheeja; Epstein, Michele; DiPalma, Joan; Aghai, Zubair H. (American Journal of Perinatology, 2018)
Objective The objective was to determine if the presence of a nasogastric (NG) feeding tube is associated with increased gastroesophageal reflux (GER) and acid exposure in preterm infants.Study Design This is a retrospective study on preterm infants [gestational age (GA) <37 weeks] who were evaluated by multichannel intraluminal impedance and pH monitoring (MII-pH) between October 2009 and March 2016. Infants were divided into two groups, NG tube present and no feeding tube. GER events per hour and the percent of time with pH <4 during a 24-hour period were then compared.Results Eighty-three infants were included, 41 had an NG tube present and 42 did not. The group without an NG tube had significantly more reflux events per hour (2.3 ± 2.9 vs. 1.3 ± 0.8, p < 0.05) even after adjusting for differences in birth weight, GA, corrected GA, and total fluid intake. There was no significant difference in acidic events per hour and acid exposure time between the two groups.Conclusion The presence of a 5-French NG tube is not associated with an increase in GER or acid exposure in preterm infants. In fact, it appears that infants fed through an NG tube have fewer episodes of GER.
Keywords: multichannel intraluminal impedance; neonates; preterm infants; pH probe; gavage feeding